2020
DOI: 10.1192/bjo.2020.67
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions for adolescents living with HIV or affected by HIV in low- and middle-income countries: systematic review

Abstract: Background Mental health difficulties and mental disorders are common in adolescents living with HIV or who are affected by HIV because of living in HIV-affected households in low- and middle-income (LMICs) countries, but little is known about the interventions that target these individuals and whether they are effective. Aims This systematic review aims to address these gaps by examining what has worked and what has not worked to support the mental health of adolescents living with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…Results from our modification assessment suggest the association between physical or sexual violence and depressive symptoms is mitigated in individuals with higher social support or self‐esteem. Although a number of interventions aimed at improving social support or self‐esteem among South African YLWH have proven ineffective, interventions from similar settings have demonstrated success [78,79]. The Zvandiri programme, which began as a single support group in Zambia, aims to ensure the physical, social and mental well‐being of YLWH to improve HIV care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Results from our modification assessment suggest the association between physical or sexual violence and depressive symptoms is mitigated in individuals with higher social support or self‐esteem. Although a number of interventions aimed at improving social support or self‐esteem among South African YLWH have proven ineffective, interventions from similar settings have demonstrated success [78,79]. The Zvandiri programme, which began as a single support group in Zambia, aims to ensure the physical, social and mental well‐being of YLWH to improve HIV care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, multiple reviews have documented that even fewer trials have tested interventions which target the mental health needs AYALH or AYAAH, particularly in LMIC, with mixed findings [9,24,29,37,38]. Due to the lack of sufficient evidence, the World Health Organization guidelines on mental health treatment and prevention for adolescents (Helping Adolescents Thrive) concluded that despite the priority of delivering mental health interventions to AYALH, no recommendations could be made and highlighted a need for highquality research on psychosocial interventions promoting AYALH mental health [39]. A similar need has been advocated for AYAAH including uninfected AYA with PHEU given the high rates of mental health problems and potential risks of perinatal exposure to ART, as well as similar psychosocial and contextual risks as AYALH [40].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to support adolescent-caregiver relationships are parenting and family strengthening programmes [ 53 55 ]. Several programmes have been developed or tailored for families with ALHIV [ 56 ] and adolescents affected by HIV [ 57 , 58 ]. For example, the Vuka programme [ 18 ] is a group-based intervention for adolescent-caregiver pairs that addresses adolescent-caregiver communication, strategies for adolescent safety in the community, and HIV knowledge and disclosure, among other topics.…”
Section: Discussionmentioning
confidence: 99%